Prevalence of extended-spectrum cephalosporin-resistant Escherichia coli in a farrowing farm: ST1121 clone harboring IncHI2 plasmid contributes to the dissemination of blaCMY-2 - Deng, Hui; Si, Hong-Bin; Zeng, Shu-Yi; Sun, Jian; Fang, Liang-Xing; Yang, Run-Shi; Liu, Ya-Hong; Liao, Xiao-Ping (Frontiers in Microbiology, 2015)
Abstract During a regular monitoring of antimicrobial resistance in a farrowing farm in Southern China, 117 Escherichia coli isolates were obtained from sows and piglets. Compared with the isolates from piglets, the isolates from sows exhibited higher resistance rates to the tested cephalosporins. Correspondingly, the total detection rate of the blaCMY-2/blaCTX-M genes in the sow isolates (34.2%) was also significantly higher than that of the piglet isolates (13.6%) (p<0.05). The blaCMY-2 gene had a relatively high prevalence (11.1%) in the E. coli isolates. MLST and PFGE analysis revealed the clonal spread of ST1121 E. coli in most (7/13) of the blaCMY-2-positive isolates. An indistinguishable IncHI2 plasmid harboring blaCMY-2 was also identified in each of the seven ST1121 E. coli isolates. Complete sequence analysis of this IncHI2 plasmid (pEC5207) revealed that pEC5207 may have originated through recombination of an IncHI2 plasmid with a blaCMY-2-carrying IncA/C plasmid like pCFSAN007427_01. In addtion to blaCMY-2, pEC5207 also carried other resistance determinants for aminoglycosides (aacA7), sulfonamides (sul1), as well as heavy metals ions, such as Cu and Ag. The susceptibility testing showed that the pEC5207 can mediate both antibiotic and heavy metal resistance. This highlights the role of pEC5207 in co-selection of blaCMY-2-positive isolates under the selective pressure of heavy metals, cephalosporins and other antimicrobials. In conclusion, clonal spread of an ST1121 type E. coli strain harboring an IncHI2 plasmid contributed to the dissemination of blaCMY-2 in a farrowing farm in Southern China. We also have determined the first complete sequence analysis of a blaCMY-2-carrying IncHI2 plasmid.